Euglycemic Hyperinsulinemia Increases Blood Pressure in Pregnant Rats Independent of Placental Antiangiogenic and Inflammatory Factors - Palei, Ana C. (Oxford University Press, 2013)
BACKGROUND: Although pregnancies associated with hyperinsulinemia and altered placental angiogenic and inflammatory factors are at increased risk for developing preeclampsia, the effects of euglycemic hyperinsulinemia on placental factors and blood pressure regulation during pregnancy are unclear. We hypothesized that chronic hyperinsulinemia results in increased placental soluble fms-like tyrosine kinase 1(sFlt-1) and tumor necrosis factor α (TNF- α) levels and hypertension in pregnant rats. METHODS: On gestational day (GD) 14, Sprague-Dawley rats were assigned as normal pregnant or pregnant + insulin. Insulin was infused subcutaneously by osmotic minipump for 5 days at a dose of 1.5 mU/kg/min. Those rats receiving insulin were supplemented with 20% glucose in drinking water to maintain euglycemia. On GD 19, mean arterial pressure (MAP) and heart rate (HR) were assessed in conscious rats by indwelling carotid catheters, followed by collections of blood, placentas, and fetuses. In addition to pl acental sFlt-1 and TNF-α levels, circulating insulin, glucose, leptin, cholesterol, triglyceride, and free fatty acid concentrations were measured. RESULTS: MAP was higher in pregnant + insulin vs. normal pregnant rats; however, HR was similar between groups. Although litter size and placental weight were comparable, fetuses from pregnant + insulin rats were heavier. Importantly, circulating insulin concentration was elevated in the pregnant + insulin group, with no change in glucose level. Moreover, circulating leptin, cholesterol, triglyceride, and free fatty acid concentrations were increased in the pregnant + insulin group. There were no differences in placental sFlt-1 and TNF-α concentrations between groups. CONCLUSIONS: In summary, sustained euglycemic hyperinsulinemia, comparable with insulin levels in preeclamptic women, can raise blood pressure in pregnancy independent of recognized placental factors associated with preeclampsia.